Portable Nuclear Magnetic Resonance Spectrometer with Birdcage Coil for Non-destructive Testing and Analysis of Metallic Materials - Mostafa Noohi; Hassan Faraji Baghtash; Habib Badri Ghavifekr (e-Journal of Nondestructive Testing)
Non-destructive testing (NDT) using nuclear magnetic resonance (NMR) spectroscopy for metallic materials is a cutting-edge technique that offers valuable insights into the structure, composition, and properties of metals without altering or damaging the material. NMR spectroscopy is a powerful analytical tool that uses the magnetic properties of atomic nuclei to provide detailed information about the molecular environment of samples. By subjecting metallic materials to NMR analysis, researchers and engineers can gain a deeper understanding of various aspects, such as the crystal structure, defects, impurities, and mechanical properties of metals. The NMR technique can detect the magnetic behavior of metal samples and provide a non-invasive tool for evaluating the quality, integrity and performance of materials. In summary, NMR-based non-destructive testing for evaluating metallic materials provides accurate, quantitative and reliable data that can support decision-making processes, optimize manufacturing methods and ensure the safety and reliability of metallic components. The ability of NMR to probe the atomic-level structure and dynamics of metals makes it an indispensable tool for research and industrial applications in fields ranging from metallurgy and engineering to aerospace and automotive industries. In this article, a portable NMR spectrometer has been designed, simulated and implemented from a small birdcage coil for the frequency range of 1 MHz to 10 MHz according to the static magnetic field. Finally, a portable NMR device for performing NDT of metallic materials is presented, which is created by using a suitable coil, a magnetic field of 230 µT and 95% homogeneity.